Goddess blesses the boats used by the Koli fishermen - Mumbai Archive Project Team (Jio Institute, 2024)
The Goddess is taken to bless the boats used by the Koli fishermen. The presence of the Goddess on the boat ensures the safety of the fishermen at sea and a bountiful catch for the rest of the year.